QUERY BY EXAMPLE: ALTERNATIF AUDIT TOOLS UNTUK MENUNJANG PENUGASAN AUDITOR DALAM PENGUJIAN SUBSTANTIF - Oviliani Yenty Yuliana; Josua Tarigan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
Along with the growth of the information technology (IT), several audit tools are developed to help the auditorto do theirduties efficiently and effectively. ACL and IDEA are the popularexamples of the audit tools nowadays. However; for small and medium public accountants (KAP) and aUsaha Kecil Menengahn (UKM) business sectors, ACL and IDEA audit tools pricing are very expensive. Moreover, based on preliminary survey, many companies have already recorded theirtransactions into a database. It motivates a study to optimize the database features that has been owned by KAP and UKM as audit tools. Therefore the companies can reduce theirinvestment. In this paper, researchers propose the use of 'Query By Example